2020
DOI: 10.1002/da.23102
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization by women sexual assault survivors after emergency care: Results of a multisite prospective study

Abstract: Background: Approximately, 100,000 US women receive emergency care after sexual assault each year, but no large-scale study has examined the incidence of posttraumatic sequelae, receipt of health care, and frequency of assault disclosure to providers. The current study evaluated health outcomes and service utilization among women in the 6 weeks after sexual assault. Methods: Women ≥18 years of age presenting for emergency care after sexual assault to twelve sites were approached. Among those willing to be cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
(82 reference statements)
2
19
0
Order By: Relevance
“…Examination of specific postevent responses that have been linked to pain in prior work should also be captured in future analyses as a mediating mechanism between exposure to trauma and pain sensitivity. 122 In conclusion, this meta-analysis found an overall pattern of trauma-related pain sensitization and implicates CS as a key mechanism by which experiencing trauma lead to altered pain processing. These mechanistic relationships highlighting how psychological experience may impact physiological pain processing can inform clinical assessments and treatments of comorbid trauma-pain conditions.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Examination of specific postevent responses that have been linked to pain in prior work should also be captured in future analyses as a mediating mechanism between exposure to trauma and pain sensitivity. 122 In conclusion, this meta-analysis found an overall pattern of trauma-related pain sensitization and implicates CS as a key mechanism by which experiencing trauma lead to altered pain processing. These mechanistic relationships highlighting how psychological experience may impact physiological pain processing can inform clinical assessments and treatments of comorbid trauma-pain conditions.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, there are individuals who may be experiencing traumatic distress related to potentially traumatic events (eg, experiences of racism, police brutality, sexual harassment) that are not currently captured in traditional trauma assessments, who are missing from research, and whose pain risk may be clinically overlooked. Type of trauma is important to consider, as both pre-event factors (eg, preexisting psychological distress, psychosocial factors, adverse childhood experiences)121 and postevent distress61,121 as well as general psychosocial factors (eg, access to health care, diagnostic validity, available coping strategies)122 are likely to play a role. Examination of specific postevent responses that have been linked to pain in prior work should also be captured in future analyses as a mediating mechanism between exposure to trauma and pain sensitivity 122…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study analyzing healthcare utilization in the 6-week period after presenting to the ED for post-assault care showed that, despite 76% of survivors reporting posttraumatic stress, depression, or anxiety, less than 40% saw a medical provider (Short et al, 2021). While lack of access to longitudinal care is a contributing factor, qualitative studies show that major reasons why survivors do not seek help or disclose their assault history to providers are shame, embarrassment, or fear of being judged or not believed (Patterson et al, 2009; Price et al, 2014; Short et al, 2021). Specifically, survivors who did not perceive their experience as matching stereotypical societal conceptions of sexual assault are hesitant to seek help (Patterson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual assault (SA) is common, with an estimated 19% of United States (US) women reporting rape and 43% reporting other forms of sexual contact during their lifetime 1 . Approximately 100,000 US women present for emergency care after SA each year, 2 yet opportunities to gain insights into the lives of women who present for emergency care after sexual assault (SA) are limited, both because such women rarely return for care or self‐identify when receiving further care, 3–5 and because few studies have assessed the life experiences of women SA survivors after SA nurse examiner (SANE) care. Qualitative studies of SA have focused largely on the receipt of health care services, 7–11 with less attention paid to survivors’ broader life experiences.…”
Section: Introductionmentioning
confidence: 99%